2008
DOI: 10.1086/527449
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Rotavirus-Associated and Non-Rotavirus-Associated Diarrhea among Nonhospitalized Individuals in Central Italy: A 1-Year Sentinel-Based Epidemiological and Virological Surveillance

Abstract: A community sentinel pediatrician-based epidemiological and virological surveillance study was conducted to estimate the incidence of gastroenteritis and laboratory-confirmed rotavirus-associated disease. The 1-year cumulative incidence of gastroenteritis in the cohort of children aged 0-5 years was 21%, with the highest rates in the 7-12-month and 13-18-month age groups (41.1% and 41.7%, respectively). Approximately one-third of gastroenteritis cases requiring an office visit or telephone consultation were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In addition to the direct protective effects of vaccination, RV vaccines may also be expected to reduce the number of cases among unvaccinated children [34]. As in other surveillance studies in Europe [1,9,11,14,32], disease burden was found to be the greatest among the youngest age groups, with even infants aged less than 3 months of age affected. As expected, almost all RVGE occurred between the months of December and May.…”
Section: Incidence Of Rvgementioning
confidence: 70%
See 2 more Smart Citations
“…In addition to the direct protective effects of vaccination, RV vaccines may also be expected to reduce the number of cases among unvaccinated children [34]. As in other surveillance studies in Europe [1,9,11,14,32], disease burden was found to be the greatest among the youngest age groups, with even infants aged less than 3 months of age affected. As expected, almost all RVGE occurred between the months of December and May.…”
Section: Incidence Of Rvgementioning
confidence: 70%
“…An earlier surveillance study conducted in seven European countries from October 2004 to September 2005 showed RV to account for one third of primary care consultations for acute GE among children aged less than 5 years, with annual incidence rates of RVGE ranging from 20.7 to 49.7 per 1,000 children-years [32]. RV was also found to account for one third of acute GE cases among children aged less than 5 years in a study in an urban primary care centre in Italy from April 2005 to April 2006 [1]. In another study in Spain, the proportion of acute GE attributable to RV among children aged less than 5 years presenting to primary care physicians was only 15% during the period from December 2003 to November 2004 [9], but increased to 25 In addition, only PCR-positive RVGE cases were included in this study.…”
Section: Incidence Of Rvgementioning
confidence: 99%
See 1 more Smart Citation
“…Another study from France confirmed this trend, showing significant differences in dehydration between rotavirus-positive and negative gastroenteritis (26.8% vs.14.7%, P < .0001) as did a study from Greece [17,46]. Further, one Italian community-based study showed that dehydration at initial presentation in primary care was associated with a higher likelihood of RVGE (OR: 1.8; 95% CI, 1.1-3; P = 0.02) [53]. …”
Section: Resultsmentioning
confidence: 91%
“…Information concerning serotype distribution over time for fully serotyped samples from children under five years of age was available for five countries (Denmark [36,50], France [25,36,51], Italy [25,52,53], Spain [25,30,36,54], and the UK [25,36,55,56]) (Figure 3). However, on examination of the evolution of genotype distribution and predominance over time, we were not able to discern any overall trends in serotype distribution within the region.…”
Section: Resultsmentioning
confidence: 99%